CHARACTERIZATION OF HEPATIC MASSES WITH DYNAMIC COMPUTERIZED TOMOGRAPHIC SCANNING: Hepatic Masses With Dynamic CT Scanning - Raza, Brig Syed Saleem; Siddiqi, Hammad Ahmad (Pakistan Armed Forces Medical Journal, 2010)
The introduction of computerized tomography (CT) has revolutionized medical imaging. It is the most important radiological investigation in the evaluation of hepatic masses; whether malignant or benign. The differentiation amongst the hepatic masses is significantly improved by difference in enhancement patterns. Different protocols have been developed and used for the evaluation of hepatic masses. The commonly used and simpler technique is the plain scan, followed by a bolus of contrast administration and then the images are taken after an interval of 25 seconds for arterial phase, 70 seconds for portal venous phase and 5 minute for equilibrium phase2